Change of cultivation parameters of asparagus (Asparagus officinalis L.) on different nutrient systems - Zsombik, László; Erdős, Zsuzsa (Acta Agraria Debreceniensis, 2014)
The experiments were conducted at the Research Institute of Nyíregyháza, Research Institutes and Study Farm, Centre for Agricultural Sciences, University of Debrecen. We have studied the shoot number, plant height and fold thickness os asparagus for 3 years. We have set a fertilization experiment on 1500 m2 of plantations in 2013. We applied fertilizer, manure and sheet manure compost. The set yield we achieved by using fertilizer treatment. The Vitalim produced the largest crop, then the Cumulus and the lowest yield Grolim. We was produced by highest green mass was observed in Vitalim and Cumulus hybrids in each year. The Grolim hybrid produced the smallest shoot and plant height but the fold thickness was longer in the other two hybrids. Overall, the Vitalim hybrid has the best production parameters and each season.